2018
DOI: 10.1186/s13000-018-0711-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the proliferation marker Ki-67 in gliomas: Interobserver variability and digital quantification

Abstract: BackgroundThe Ki-67 Labelling Index (LI) is used as an ancillary tool in glioma diagnostics. Interobserver variability has been reported and no precise guidelines are available. Nor is it known whether novel digital approaches would be an advantage. Our aim was to evaluate the inter- and intraobserver variability of the Ki-67 LI between two pathologists and between pathologists and digital quantification both in whole tumour slides and in hot spots using narrow but diagnostically relevant intervals.MethodsIn s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 21 publications
1
23
0
2
Order By: Relevance
“…Besides, immunohistochemistry of TRIM31 expression in 80 glioma samples further confirmed that TRIM31 was overexpressed in high grade gliomas ( Figure 1B), since immunohistochemistry can be used to localize, characterize and quantify antigens in tissues and cells [17]. From the Spearman rank test result in Figure 1C, it's obvious that there was a positive relationship between TRIM31 and Ki-67 expression (r=0.779, p<0.001), and Ki-67 is widely used as an ancillary tool for the diagnosis and prognosis of glioma [18]. The clinicopathological features of the 80 samples were presented in Table 1, which included 25 cases of Grade II gliomas, 31 cases of Grade III gliomas and 24 cases of Grade IV gliomas.…”
Section: Resultsmentioning
confidence: 55%
“…Besides, immunohistochemistry of TRIM31 expression in 80 glioma samples further confirmed that TRIM31 was overexpressed in high grade gliomas ( Figure 1B), since immunohistochemistry can be used to localize, characterize and quantify antigens in tissues and cells [17]. From the Spearman rank test result in Figure 1C, it's obvious that there was a positive relationship between TRIM31 and Ki-67 expression (r=0.779, p<0.001), and Ki-67 is widely used as an ancillary tool for the diagnosis and prognosis of glioma [18]. The clinicopathological features of the 80 samples were presented in Table 1, which included 25 cases of Grade II gliomas, 31 cases of Grade III gliomas and 24 cases of Grade IV gliomas.…”
Section: Resultsmentioning
confidence: 55%
“…Thus, data are scarce regarding digital determinations of MIB-1 PIs in human meningiomas. However, similar studies have been performed in other tumors, such as breast cancer, 19 gliomas, 20 gastrointestinal stromal tumors, 21 and prostate cancer. 22 In those studies, a generally good correlation was established between manual and digital determinations of MIB-1 PIs, but the prognostic aspects varied.…”
Section: Introductionmentioning
confidence: 68%
“…Ki‐67 was present in all active phases of cell cycle, but absent from resting cells . The prognostic value of Ki‐67 for survival and tumor recurrence have been confirmed in some cancer types, such as breast cancer, prostate cancer and neuroendocrine cancer . It also shows prognostic potential in ESCC .…”
Section: Resultsmentioning
confidence: 90%